2016
DOI: 10.1002/anie.201607786
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Liquid‐Crystalline Polymer Brushes Formed by Surface Segregation and Self‐Assembly

Abstract: High-density polymer brushes on substrates exhibit unique properties and functions stemming from the extended conformations due to the surface constraint. To date, such chain organizations have been mostly attained by synthetic strategies of surface-initiated living polymerization. We show herein a new method to prepare a high-density polymer brush architecture using surface segregation and self-assembly of diblock copolymers containing a side-chain liquid-crystalline polymer (SCLCP). The surface segregation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
(110 reference statements)
1
27
0
Order By: Relevance
“…The brighter skin layer and the darker underlayer are assigned to the PCNAz domain and PS domain, respectively, because the PS part with a higher phenyl group density is more strongly stained by RuO4 oxidants. [ 21a ] Thus, a PCNAz block chain monolayer forms at the film surface. Compared with the average unit numbers of the PCNAz block, the estimated extension of the PCNAz chain is 87% for the all‐trans‐zigzag conformation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The brighter skin layer and the darker underlayer are assigned to the PCNAz domain and PS domain, respectively, because the PS part with a higher phenyl group density is more strongly stained by RuO4 oxidants. [ 21a ] Thus, a PCNAz block chain monolayer forms at the film surface. Compared with the average unit numbers of the PCNAz block, the estimated extension of the PCNAz chain is 87% for the all‐trans‐zigzag conformation.…”
Section: Resultsmentioning
confidence: 99%
“…To attain such a structure, we adopt a surface segregation strategy using a diblock copolymer with an Az side‐chain liquid crystalline polymer (SCLCP). [ 21 ] We previously demonstrated that a spin‐cast film of polystyrene (PS) containing a small amount of a diblock copolymer of SCLCP connected with a PS block segregates the surface and forms a high‐density SCLCP brush via self‐assembly. [ 21 ] The PS block acts as a laterally mobile anchoring part to form a high‐density LC polymer brush on the PS film surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter exhibits unique properties because of the stretched chain conformations, and dense LC polymer brushes can be prepared via e.g. surface segregation and self-assembly of diblock LC polymer molecules [48]. Another wide and technologically important class of LC polymer brushes are photo-sensitive brushes that contain chromophoric, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The cornerstones of such occurrences in physical properties are the conformation , orientation , and arrangement of polymer chains. In the second half of the 1990s, the observation of one molecular chain was first achieved, in 3 days, owing to the formation of Langmuir–Blodgett (LB) films and the use of high‐resolution atomic force microscopy (AFM) technology .…”
Section: Introductionmentioning
confidence: 99%